Synthesis of Dibenzo[b,h][1,5]naphthyridin-7(12H)-ones: The Pictet–Spengler Reaction versus a Rearrangement of 4-Phenyl[1,3]oxazolo[4,5-c]quinolines - Shatsauskas, Anton L.; Kirnosov, Sergey A.; Keyn, Ekaterina S.; Shuvalov, Vladislav Yu.; Kostyuchenko, Anastasia S.; Fisyuk, Alexander S. (Synthesis, 2024)
Two approaches were proposed for the synthesis of dibenzo[b,h][1,5]naphthyridin-7(12H)-ones. The one-step method based on the Pictet–Spengler reaction of 3-amino-2-phenylquinolin-4(1H)-one with aromatic aldehydes requires heating in a strong acidic media, which leads to significant limitations on the possible products. The second approach is based on the conversion of 3-amino-2-phenylquinolin-4(1H)-one to 4-phenyl[1,3]oxazolo[4,5-c]quinolines followed by rearrangement under the action of AlCl3. A significant advantage of the two-step synthesis is the possibility of obtaining a wider range of dibenzo[b,h][1,5]naphthyridin-7(12H)-ones, including those not available using the Pictet–Spengler reaction.
Keywords: heterocycles; rearrangement; Lewis acid; annulations; 1,5-naphthyridine; Pictet–Spengler reaction